Interpretation and Assessment of Islamic Antiquities within the hydraulic Heritage System at Al-Muwaqqar - Al-Naser, Rawan Abdallah (Journal of Humanities & Social Sciences, 2022)
This research focusses on the Islamic antiquities and the related hydraulic system of the Al-Muwaqqar region. The problem of the study is to answer the following questions (1) Which antiquities survive today in Muwaqqar? How can they be described? (2) What kind of conclusions about their original appearance and their functions can be drawn from the existing remnants in combination with earlier reports? (3) What was the system of water collection and transportation? (4) Which is the interrelation between the water system and the dwellings and their environment?The study follows different methodological approaches to the study of early Islamic architecture. The detailed investigation of the ruins, which the author conducted in Al-Muwaqqar in 2019 and 2020, is followed by their translation into written and drawn documents. On the basis of previous reports and a systematic survey of these surviving original remnants, the present research will give by applied quantitative as well qualitative methods an outline on the architectural structures with reconstruction proposals. It will discuss also how these monuments were related to each other functionally and how the Umayyad architects and engineers solved the problem of the limited water resources in this transitional area with low rainfalls. This creates an overall picture that gives the reader of the study and the future visitor of the place an idea about the place in its actual condition. The study will create awareness by interpretation, which is a precondition for raising the value of these monuments in the awareness of the local community and for visitors. The research recommended that the architectural monuments of Al-Muwaqar be placed within the cultural heritage at great risk of the Kingdom of Jordan.
Keywords: Al-Muwaqqar; Umayyad architecture; hydraulic system; Islamic antiquities